1970
DOI: 10.1111/j.1600-0722.1970.tb02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida in oral leukoplakias A histologic and exfoliative cytologic study

Abstract: Abstract— Oral leukoplakias and clinically normal mucosa of 226 patients were examined by smear or biopsy or both. From the biopsies eleven consecutive sections were evaluated, the first section being stained with hematoxylin‐eosin and the following ten with PAS. Clinically normal mucosa did not show Candida, whereas Candida was present in 31 % of the biopsied leukoplakias. Eight of the 30 Candida‐invaded biopsies did not contain the hyphae in all ten PAS‐stained sections. Had only one section been evaluated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

1974
1974
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
2
22
0
2
Order By: Relevance
“…The cellular changes often include hyperplasia, cellular atypia, mild or severe dysplasia, and in situ or invasive carcinoma (Cawson and Lehner, 1968;Pindborg, 1971;Roed-Petersen et al, 1970).…”
Section: The Possible Role Of Candida In Oral Carcinogenesismentioning
confidence: 99%
“…The cellular changes often include hyperplasia, cellular atypia, mild or severe dysplasia, and in situ or invasive carcinoma (Cawson and Lehner, 1968;Pindborg, 1971;Roed-Petersen et al, 1970).…”
Section: The Possible Role Of Candida In Oral Carcinogenesismentioning
confidence: 99%
“…Smoking and alcohol exposure are not invariable-e.g., they were not seen in half the cases of the Danish study )-so other factors should be considered. One factor may be Candida albicans, since this has been associated with malignant development in some leukoplakias (lepsen and Winther, 1965;Renstrup, 1970;Roed-Petersen et al, 1970;Cawson and Binnie, 1977), and such yeasts have been identified in OLP (Holmstrup and Dabelsteen, 1974;Simon and Hornstein, 1980;Krogh et al, 1987a,b).…”
Section: Candidosismentioning
confidence: 99%
“…Jepsen and Winther (1965) isolated C. albicans alone in 91% of speckled leukoplakias. Roed-Petersen et al (1970) succeeded in culturing C.…”
Section: (62) Identification Of Candida Speciesmentioning
confidence: 99%
“…According to several reports, the leukoplakias that harbor candidal hyphae appear to constitute from 7 to 50% of all leukoplakias (Jepsen and Winther, 1965;Roed-Petersen et al, 1970;Daftary et al, 1972;Roed-Petersen and Pindborg, 1973;Bánóczy, 1982;Krogh et al, 1987b). Lehner (1971) has suggested that differential counts of pyroninophilic monocytes be carried out to distinguish between candidal and non-candidal leukoplakias.…”
Section: (12) Epidemiological and Demographic Aspects Of Chc: Incidementioning
confidence: 99%